2023
DOI: 10.4269/ajtmh.22-0496
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antenatal Azithromycin and Monthly Sulfadoxine-Pyrimethamine on Maternal Malaria during Pregnancy and Fetal Growth: A Randomized Controlled Trial

Abstract: Maternal malaria and infections during pregnancy are risk factors for fetal growth restriction. We assessed the impact of preventive treatment in pregnancy on maternal malaria and fetal growth. Between 2003 and 2006, we enrolled 1,320 pregnant Malawian women, 14–26 gestation weeks, in a randomized trial and treated them with two doses of sulfadoxine-pyrimethamine (SP, control) at enrollment and between 28–34 gestation weeks; with monthly SP from enrollment until 37 gestation weeks; or with monthly SP and azith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We have identified 20 RCTs with 56,381 participants 8 , 10 , 11 , 13 , 15 , 16 , 24 , 25 , 26 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 [ Fig. 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have identified 20 RCTs with 56,381 participants 8 , 10 , 11 , 13 , 15 , 16 , 24 , 25 , 26 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 [ Fig. 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent trials from high-income countries where the prevalence of untreated RTIs and malaria was low in pregnancy failed to show beneficial effects on foetal and neonatal well-being. 15 , 16 , 24 Instead, they consistently showed that single-dose intrapartum azithromycin prophylaxis was associated with reduced SSIs, endometritis, and maternal mortality. 10 , 13 , 15 Hence, recently, the focus has shifted from neonatal to maternal outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Chloroquine was not well tolerated in pregnancy trials nor were attempts at substituting SP with mefloquine, amodiaquine or azithromycin. [34][35][36] IPTp with dihydroartemisin-piperaquine (DP) is the most promising alternative to IpTP-SP perhaps because of the long half-life of piperaquine that may serve as prophylaxis against future mosquito bites as well as clearing any parasites sequestered in the placenta at the time of administration. Compared with IPTp-SP, IPTp-DP was associated with a lower risk of clinical malaria, peripheral parasitemia during pregnancy, and placental malaria at delivery.…”
Section: Chemoprophylaxismentioning
confidence: 99%
“…SP resistance has led researchers to evaluate alternative antimalarials for chemoprophylaxis in pregnancy, including the reintroduction of chloroquine, an early antimalarial with widespread resistance whose efficacy in Africa reappeared after years of not recommending its use 33 . Chloroquine was not well tolerated in pregnancy trials nor were attempts at substituting SP with mefloquine, amodiaquine or azithromycin 34–36 . IPTp with dihydroartemisin-piperaquine (DP) is the most promising alternative to IpTP-SP perhaps because of the long half-life of piperaquine that may serve as prophylaxis against future mosquito bites as well as clearing any parasites sequestered in the placenta at the time of administration.…”
Section: Prevention Of Malaria In Pregnancymentioning
confidence: 99%